A review of the pharmaceutical exposome in aquatic fauna. (August 2018) - Miller, Thomas H.; Bury, Nicolas R.; Owen, Stewart F.; MacRae, James I.; Barron, Leon P.
Abstract: Pharmaceuticals have been considered 'contaminants of emerging concern' for more than 20 years. In that time, many laboratory studies have sought to identify hazard and assess risk in the aquatic environment, whilst field studies have searched for targeted candidates and occurrence trends using advanced analytical techniques. However, a lack of a systematic approach to the detection and quantification of pharmaceuticals has provided a fragmented literature of serendipitous approaches. Evaluation of the extent of the risk for the plethora of human and veterinary pharmaceuticals available requires the reliable measurement of trace levels of contaminants across different environmental compartments (water, sediment, biota - of which biota has been largely neglected). The focus on pharmaceutical concentrations in surface waters and other exposure media have therefore limited both the characterisation of the exposome in aquatic wildlife and the understanding of cause and effect relationships. Here, we compile the current analytical approaches and available occurrence and accumulation data in biota to review the current state of research in the field. Our analysis provides evidence in support of the 'Matthew Effect' and raises critical questions about the use of targeted analyte lists for biomonitoring. We provide six recommendations to stimulate and improve future research avenues. Graphical abstract: Image 1 Highlights: Occurrence and accumulation of pharmaceuticals in aquatic fauna is presented. Evidence of the Matthew Effect from biased pharmaceutical pre-selection. Field versus laboratory derived accumulation factors showed a large disparity. Specific accumulation is pronounced for liver and bile over other tissues. Recommendations for advancements within environmental toxicology are proposed. Abstract : The determination of the pharmaceutical exposome in aquatic fauna is critical to understanding the extent of contamination and the potential risk in the environment.